Symptomatology, pathophysiology and treatment perspectives of "long COVID" syndrome - Łukasz Dobrek (Polish Pharmaceutical Society, 2024)
The year 2020 was marked in history by the pandemic of SARS-CoV-2 infection. The relatively quick introduction of vaccinations and antiviral drugs (e.g. orally administered molnupiravir, nirmatrelvir/ritonavir) allowed the global nature of COVID-19 to be controlled after more than 2 years. Currently, attention is also drawn to the chronic consequences of SARS-CoV-2 infection in recovered patients, referred to as post-COVID syndrome and commonly known as "long COVID". Estimates indicate that long COVID develops in more than half of patients after the acute phase of infection, especially in hospitalized patients with severe COVID-19, with dysfunction of immune mechanisms in the course of cancer or AIDS, and with comorbidities, such as asthma, type 2 diabetes, hypertension, obesity, depression and anxiety disorders, and hypothyroidism. Long COVID is characterized by multiple symptoms arising from all body systems, and chronic fatigue, headache, impaired attention and concentration ("brain fog"), hair loss and shortness of breath are the most frequently observed disturbances in adult patients. The pathophysiology of long COVID is complex and, according to numerous theories, the symptoms of post-COVID syndrome result from the persistence of SARS-CoV-2 in peripheral tissues after the acute phase of infection, which maintains a "low-grade", chronic inflammation, activation of previously latent other viral infections, developing thrombotic events in the microcirculation of peripheral vascular beds, dysbiosis of the digestive system and respiratory tract, and disturbances of the autonomic system. The currently used vaccines, by reducing the risk of severe COVID-19, also indirectly reduce the risk of long COVID development. There are ongoing clinical studies assessing the usefulness of various drugs that have been routinely used so far in the treatment of other diseases (sulodexide, pirfenidone, vortioxetine, fampridine, gabapentin, ivabradine, beta blockers, statins, oral anticoagulants, antileukotriene drugs and glucocorticoids, ivermectin) and active compounds usually found in dietary supplements (coenzyme Q10, vitamins, omega-3 fatty acids, probiotics, genistein, lactoferrin) in the long COVID pharmacotherapy. Due to the still incomplete pathophysiological description and the possibility of specific treatment of long COVID, further research is required to expand knowledge in this issue.